Éthique, poétique et esthétique d’un réenchantement du monde : Du bonheur d’habiter la maison au bonheur d’habiter le monde - Hotton, Elodie (BACHELARD STUDIES - ÉTUDES BACHELARDIENNES - STUDI BACHELARDIANI, 2020)
Gaston Bachelard transcends the opposition between the well-being inside the house and the hostility of the world outside by extending the well-being experienced in the reveries of inhabited spaces from the house to the oneiric world. This lays the groundwork for the re-enchantment of the real world. Looking at what surrounds us with the children’s eyes full of wonder and taking our reveries seriously would reenchant the world esthetically and poetically. Since Bachelard’s theory of moral imagination states that the moral imagination prepares ethical actions, this article demonstrates how the well-being experienced in the reveries of inhabited spaces turns into a being well and acting well in the world. Keywords: moral imagination, poetics of space, poetic reveries, reenchanted world, oneiric well-being